الآثار المترتبة على اتفاق ونطاق التحكيم في عقود الشراكة - عمروني, جيلالي (جامعة الوادي - University of Eloued, 2023)
للتحكيم تأثيران مهمان أحدهما سلبي والآخر إيجابي فالسلبي هو إنكار حق السلطة القضائية في مراجعة المنازعات التي اتفق الأطراف على حلها عن طريق التحكيم ، ولا يعني هذا الخلاف أن المحاكم تفقد اختصاصها تمامًا ، بل تفقد سلطتها فقط في مراجعة النزاع. أما بالنسبة للأثر الإيجابي ، فإن هذا ينطوي على تسوية النزاع عن طريق التحكيم ، واعتماد الحكم الصادر فيه والنظر فيه كما لو كان قد صدر من قبل المحكمة المختصة أصلاً بالنزاع. . ولهذا كان منح لهيئة خاصة مؤقتة حق دراسة النزاع والبت فيه وهي هيئة التحكيم ، وهذا التأثير له حدوده ؛ وهو أثر غير مكتمل لا يمتد إلى القضايا التي لا يتخصص التحكيم في الفصل فيها. Arbitrage has two important effects, one negative and the other positive:The negative is the denial of the right of the judicial authority to review disputes which the parties have agreed to resolve by arbitration,and this dispute does not mean that the courts completely lose their jurisdiction, but only lose their authority to review the dispute. As for the positive effect, this involves the settlement of the dispute by arbitration, the adoption of the judgment rendered therein and its consideration as if it had been rendered bythe court originally competent in the dispute. Granting a temporary special body the right to examine and decide the dispute, which is the arbitration panel, and this effect has its limits; It is an incomplete effect that does not extend to issues that arbitration does not specializein separating
The implications of the agreement and scope of arbitration in partnership contracts
مقال
Keywords: سلطة قضائية، منازعات، تحكيم تجاري ، تسوية نزاعات ، محكمة مختصة; Judicialauthority, disputes,commercial arbitration, settlement of disputes, specialized court